IMPLEMENTATION OF TAX HOSTAGE (GIJZELING) AS AN ULTIMUM REMEDIUM IN TAX COLLECTION. - Pingkan Meylinda Palar, Vincensya; Ispriyarso, Budi (fakultas hukum universitas PGRI Semarang, 2024)
This research aims to determine the regulation and implementation, as well as the factors considered by the government in applying tax hostage (gijzeling) as an ultimum remedium in tax collection, as well as to understand the tax hostage policy reviewed from three fundamental legal values. This research is normative research using the literature study approach method, where data collection refers to previous research, journals, books, documents, and other reading sources. From this research, it can be understood that the existence of tax hostages as an ultimum remedium has a positive influence on increasing tax compliance and awareness in Indonesia. This is supported by the role of tax detention, which is considered to provide psychological pressure, shame, and deterrence to taxpayers. Furthermore, when reviewed from three fundamental legal values, the tax hostage policy can be said to have met the values of legal justice, legal certainty and legal expediency.